Análisis de costos de seguridad y salud laboral en la rentabilidad de las empresas industriales de la región Loreto 2014-2018 - Cornelio Chujutalli, Miguel Angel (2023)
Industrial companies in the Loreto Region are divided into two: primary manufacturing and non-primary manufacturing. Occupational health and safety costs are: production operating expenses, sales and distribution expenses; and administration expenses. The objective of this research is to analyze the influence of occupational health and safety costs on the profitability of industrial companies in the Loreto Region, 2014 - 2018. For this, this quantitative research was carried out, correlational level and nonexperimental design. The research concludes that occupational health and safety costs directly influence the profitability of industrial companies in the Loreto Region, since the statistical test shows that the Correlation Coefficient was r = 0.898; and the Coefficient of Determination was R2 = 0.806. The costs of occupational health and safety in the Loreto region carried out in the 2014-2018 period amounted to S/. 39,947.00 thousand; which results in an annual average of S/. 7,989.40 thousand. The profitability of the industrial companies of the Loreto region was determined in the period 2014 - 2018, with respect to the NPV, the sectors of Oil Refining, Soft Drinks, Sawn Wood, Tripley and Motorcycles and motokar predominate. When the IRR is analyzed, the category "Soft drinks" stands out in the first place with a value of 459.61%. When the B/C is analyzed, the category "Soft drinks" stands out first with a value of 29.84. When the ROA is analyzed, the item "Canned Heart of Palm" stands out in the first place with a value of 92.54%. When the ROI is analyzed, the category "Motors for wells" stands out in the first place with a value of 70.82%. When the ROE is analyzed, the item "Malted drinks" stands out in the first place with a value of 41.00%, showing variations with a positive trend.